A three-month course of lamivudine therapy in HBeAg-positive hepatitis B patients with normal aminotransferase levels - Kendal YALÇIN; Halil DEĞERTEKİN and Ömer Faruk KOKOĞLU and Celal AYAZ (Turkish Journal of Gastroenterology, 2019)
-